2019
DOI: 10.1177/1368430219827361
|View full text |Cite
|
Sign up to set email alerts
|

Examining the role of perceived prestige in the link between students’ subjective socioeconomic status and sense of belonging

Abstract: Low socioeconomic status (SES) students have a lower sense of belonging to college than high-SES students. Due to the importance of sense of belonging in the college pathway, understanding the reason for this relation is particularly important. Here, we argue that in addition to having less access to resources, low-SES students in the college context also perceive themselves as having lower prestige than their high-SES counterparts. Thus, in the present research, we tested perceived prestige as a mediator of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 101 publications
3
21
0
Order By: Relevance
“…As in the case of objective SES, subjective SES is commonly assessed using the MacArthur SSS scale in undergraduate (Jury et al, 2019;Loeb and Hurd, 2019) and community-based (Bjornsdottir et al, 2017;Wang et al, 2019) samples. However, studies that use this measure among adolescents are becoming more frequent (e.g., Joffer et al, 2019;Moor et al, 2019).…”
Section: Objective and Subjective Socioeconomic Statusmentioning
confidence: 99%
“…As in the case of objective SES, subjective SES is commonly assessed using the MacArthur SSS scale in undergraduate (Jury et al, 2019;Loeb and Hurd, 2019) and community-based (Bjornsdottir et al, 2017;Wang et al, 2019) samples. However, studies that use this measure among adolescents are becoming more frequent (e.g., Joffer et al, 2019;Moor et al, 2019).…”
Section: Objective and Subjective Socioeconomic Statusmentioning
confidence: 99%
“…For example, this may come from the experiencing downward social comparisons that may conflict with where individuals feel they stand in a given social hierarchy (see [ 23 , 95 , 128 ]) and a perceived lack of fit in certain elite institutions (e.g. universities: [ 89 , 93 , 94 , 97 ]). Future research could shed more light on this question by using a measure that directly measures ambivalence towards the rich and the poor.…”
Section: Discussionmentioning
confidence: 99%
“…However, the implications of contact with the rich probably differ depending on the income of the student or the student's family. In low-income but highly educated individuals, pro-wealthy associations brought about by familiarity with upper-class peers may be offset to some degree by difficulties in navigating cultural differences across class lines [89,[93][94][95]. Indeed, research has identified the academic context as a potential threat to the class identity of middle-class or first-generation students at elite universities, resulting in greater stress [96] and need for self-regulation [97].…”
Section: Cultural Fit Accountmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has repeatedly shown that disadvantaged social groups experience a poorer sense of belonging in school than more advantaged social groups (Freeman, Anderman, & Jensen, 2007; Ostrove & Long, 2007). Jury, Aelenei, Chen, Darnon, and Elliot (2019) investigate the reason why students from working-class backgrounds report lower sense of belonging in higher education than their peers from upper middle-class backgrounds. The authors hypothesize that the relationship between social class and sense of belonging is mediated by perceptions of one’s prestige in academia.…”
Section: Educational Structure and Symbolic Disqualificationmentioning
confidence: 99%